3(y-2)=1-3y

Simple and best practice solution for 3(y-2)=1-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-2)=1-3y equation:


Simplifying
3(y + -2) = 1 + -3y

Reorder the terms:
3(-2 + y) = 1 + -3y
(-2 * 3 + y * 3) = 1 + -3y
(-6 + 3y) = 1 + -3y

Solving
-6 + 3y = 1 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
-6 + 3y + 3y = 1 + -3y + 3y

Combine like terms: 3y + 3y = 6y
-6 + 6y = 1 + -3y + 3y

Combine like terms: -3y + 3y = 0
-6 + 6y = 1 + 0
-6 + 6y = 1

Add '6' to each side of the equation.
-6 + 6 + 6y = 1 + 6

Combine like terms: -6 + 6 = 0
0 + 6y = 1 + 6
6y = 1 + 6

Combine like terms: 1 + 6 = 7
6y = 7

Divide each side by '6'.
y = 1.166666667

Simplifying
y = 1.166666667

See similar equations:

| 8n-11n=6 | | 67+7x-5x=109 | | 4x+23-3x=9+5x | | 3(y-2)=1-3y/5 | | -4(6+7x)=-360 | | -6(y+2)=18 | | X^2+3*x-24=0 | | X-9+6=2x-14 | | 6×^2/5=4 | | 6×^2=5/=4 | | -2(10+x)=-4 | | x^4+18(x^2)+81=0 | | 5(-3x-1)=-50 | | 81-33= | | x-355+80+2x=2425 | | -2,3;m=1/3 | | -2(-1x+8)=-28 | | 4(7+6x)=172 | | 9a^4=49 | | h(7)=3/2(7)-2 | | 5-14=z/-9 | | 0.2x+13+x=0.1(x+40)+4 | | p^2+6p-4=-9 | | (5x-2z)(5x+8z)= | | 3(1-2x)=-69 | | 30-12v=-12v-4 | | N^2+4n-15=-3 | | F(x)=x^2-17 | | 8(2x-3)/3=(8x-1)/7 | | 5x+12-3x=9+4x-5 | | 3z=15-8 | | g(-2)=-5(-2)-9 |

Equations solver categories